Resposta aguda do exercício físico em diferentes intensidades sobre os marcadores inflamatórios em adolescentes obesos - Santos, Géssika Castilho dos (2016)
The increase in the prevalence of obesity has provided greater emphasis on comorbidities and complications arising from this framework. Several factors are involved in the etiology of obesity, among them environmental, behavioral, psychological, physiological and genetic. One of the main concerns related to obesity is the state of chronic low-grade inflammation of white adipose tissue, resulting from increased fat mass in the organism, which is associated with chronic diseases. The practice of physical exercise in obese adolescents is of great value, as both acute and chronic responses can minimize low-grade inflammation in the organism of these individuals. In this sense, this investigation aimed to verify the acute effects of continuous exercise on inflammatory markers in obese adolescents during activity on a treadmill at intensities of 55% and 75% of VO2peak. The study included 10 obese adolescents of both sexes between 15 and 16 years of age. Obesity was characterized by the body mass index (BMI) and by determining the nutritional status of the adolescents according to the reference tables from the Centers for Disease Control and Prevention: obesity ≥ 95th percentile for age and sex. The prediction of aerobic power was conducted through the progressive treadmill test and the modified BALKE protocol was used. Inflammatory markers were analyzed through the Chemiluminescence method. The volunteers attended the laboratory, three times; the 1st being for the VO2peak evaluations; the 2nd for the exercise at 55%; and the 3rd for the exercise at 75%, with a one week interval between each visit. For statistical analyzes the independent Student t test was used, ANOVA for repeated measures with two factors was used to determine significant differences between the respective intensities and between times; the significance level adopted was 5% (p <0.05). The results indicated that 30 minutes of moderate aerobic exercise resulted in significant changes in the circulating levels of TNF-α (6.23 ± 1.64 to 7.03 ± 1.49) and IL-6 (3.35 ± 1.53 to 3.85 ± 1.73). The vigorous aerobic exercise session did not cause significant changes statistically speaking; there was an increase in the concentration of IL-6 (3.33 ± 0.96 to 3.63 ± 1.09) and a decrease in TNF-α (6.82 ± 1.22 to 6.48 ± 1.48) and IL10 (5.41 ± 1.29 to 5.13 ± 0.41). From the results of this study, it can be concluded that a single moderate intensity 30 minute long exercise session induced acute responses in inflammatory markers in obese adolescents.